Global corruption from a geographic perspective - Warf, Barney (Cham : Springer International Publishing : Imprint: Springer, 2019)
This monograph explores the nature of corruption around the world fr om a geographic perspective. It focuses on historical context and cultu ral factors. Readers will learn that though corruption is pervasive, ge ography greatly shapes its character. This book will offer a better und erstanding of the level of corrupt activity in any given country. The b ook analyzes an array of countries and regions. Coverage ranges from de mocratic societies, where corruption is low due to high rates of litera cy and a free press, to the most corrupt places, where centralized powe r structures and lack of a free media allow corruption to unfold unimpe ded. Anti-corruption campaigns and their effectiveness are also reflect ed upon. In addition to data from Transparency International, the text examines relevant political events. In each case, the analysis focuses on the major actors and institutions involved; the cultural norms that often regard corruption as a normal part of doing business; and the att empts by foreign and domestic actors to minimize corruption. This book will help readers better understand the causes and consequences of corr uption, as well as its type and severity varies widely across the plane t. It will appeal to students, researchers, policy makers, and interest ed general readers.
Chapter 1. Introduction -- Chapter 2. Geographies of Latin American Corruption -- Chapter 3. European Corruption in Geographic Perspective -- Chapter 4. Spatiality of Corruption in the Middle East and North Afr ica -- Chapter 5. Geographies of Sub-Saharan African Corruption -- Chap ter 6. Geographically Uneven Landscapes of Asian Corruption -- Chapter 7. Corruption in Oceania -- Chapter 8. Corruption in the United States and Canada -- Chapter 9. Conclusions -- Chapter 10. References.
Description based on publisher-supplied MARC data.
Keywords: Development economics; Economic development; Economic geography; Human geography; Law and economics; Physical geography